Review Artikel Bentuk Sel Epidermis Stomata Pada Tanaman Adam Hawa (Rhoe Discolor) Sebagai Sumber Biologi Sel - Queenara Yulianingtyas, Mutia; Mustakim, Ardi (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
Stomata are small pores located in the epidermis of leaves, which function important in gas exchange between plants and the environment. Each stomata is flanked by a pair of guard cells that regulate its opening, allowing the entry of carbon dioxide (CO2) for photosynthesis and the exit of oxygen (O2) and water vapor. Stomata play their role in the processes of photosynthesis, respiration, temperature and humidity regulation. Every plant has stomata, but each plant has a different size and density of stomata. This is caused by environmental factors and plant genetics. There are also different types of stomata in plants, some are anomostic, anisocytic, parastic, diastic and actinocytic. For this reason, further research is needed regarding the analysis of the shape and characteristics of stomata cells in Adam Eve (Rhoe Discolor) plants. The results of the research show that the stomata on Adam Eve have a unique shape like a bean or like a kidney, with varying sizes depending on environmental conditions and different plant genetics. Research also found that the stomata in Adam and Eve have an anomostic type. These findings provide important insight into the shape and role of stomata in the context of the growth of ornamental plants such as Adam's Eve leaves (Rhoe Discolor).